2020
DOI: 10.24880/maeuvfd.732352
|View full text |Cite
|
Sign up to set email alerts
|

Holştayn Düve ve İneklerde Serum Anti Müllerian Hormon Düzeyleri ile Fertilite İlişkisinin Araştırılması

Abstract: ÖZSığırlarda Anti Müllerian Hormon (AMH) konsantrasyonları ile antral folikül sayısı pozitif olarak ve yüksek seviyede ilişkilidir. Bu nedenle ovaryum rezervinin belirlenmesinde, oosit kalitesi, süperovulasyon cevabı, fertilite, verim ömrü gibi kriterlerin belirlenmesi için biyomarker olarak kullanılabilmektedir. Bu çalışmada inek ve düvelerde serum AMH düzeyleri ile fertilite parametreleri arasında olası ilişkilerin ortaya konulması amaçlanmıştır. Araştırmada 44 düve ve 40 inek materyal olarak kullanıldı. İne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…( 2018 ) documented a wide range of plasma AMH concentrations in cows, spanning from 0.013 to 0.898 ng/mL, with an average AMH level of 0.293 ng/mL. Saltik & Cetin ( 2020 ) conducted a study encompassing both heifers and cows, revealing a spectrum of AMH concentrations ranging from 0.001 to 0.700 ng/mL. Furthermore, investigations on heifers have shown that AMH levels fluctuate between approximately 0.05 and 0.50 ng/mL (Ireland et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 2018 ) documented a wide range of plasma AMH concentrations in cows, spanning from 0.013 to 0.898 ng/mL, with an average AMH level of 0.293 ng/mL. Saltik & Cetin ( 2020 ) conducted a study encompassing both heifers and cows, revealing a spectrum of AMH concentrations ranging from 0.001 to 0.700 ng/mL. Furthermore, investigations on heifers have shown that AMH levels fluctuate between approximately 0.05 and 0.50 ng/mL (Ireland et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%